Numerical analysis of a modified evacuated tubes solar collector - Sato, A. I. [UNESP]; Scalon, V. L. [UNESP]; Padilha, A. [UNESP] (My University, 2012)
The need for renewable energy sources, facing the consequences of Climate Change, results in growing investment for solar collectors’ use. Research in this field has accompanied this expansion and evacuated tube solar collector stands as an important study focus. Thus, several works have been published for representing the stratification of the fluid inside the tubes and the reservoir, as well as analytical modeling for the heat flow problem. Based on recent publications, this paper proposes the study of solar water heating with evacuated tubes, their operation characteristics and operating parameters. To develop this work, a computational tool will be used-in this case, the application of computational fluid dynamics (CFD) software. In possession of the implemented model, a numerical simulation will be performed to evaluate the behavior of the fluid within this solar collector and possible improvements to be applied in the model.
Keywords: Computational fluid dynamics; Evacuated tube; Numerical analysis; Solar collector